1990
DOI: 10.1289/ehp.9089175
|View full text |Cite
|
Sign up to set email alerts
|

The caffeine breath test and caffeine urinary metabolite ratios in the Michigan cohort exposed to polybrominated biphenyls: a preliminary study.

Abstract: A field biochemical epidemiology study was conducted using the Michigan cohort consisting of 51 rural residents exposed to polybrominated biphenyls (PBB). The study had three major objectives: a) to determine the serum half-life of the major PBB congener, hexabromobiphenyl (HBB), in the human, b) to determine if the PBB-exposed subjects had elevated cytochrome P-450I function as determined by the caffeine breath test (CBT) and the caffeine urinary metabolite ratio (CMR), and c) to determine the applicability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 27 publications
3
16
0
Order By: Relevance
“…For the CYP1A2 substrate [ 13 C]-caffeine, Park et al observed a significant correlation between 1 h single DOB 13 CO 2 / 12 CO 2 ratios and plasma [ 13 C]-caffeine clearance [132]. These results were in agreement with previous studies, in which excellent correlations between caffeine breath test results and caffeine clearance were found [133][134][135][136].…”
Section: Exhaled Breathsupporting
confidence: 82%
“…For the CYP1A2 substrate [ 13 C]-caffeine, Park et al observed a significant correlation between 1 h single DOB 13 CO 2 / 12 CO 2 ratios and plasma [ 13 C]-caffeine clearance [132]. These results were in agreement with previous studies, in which excellent correlations between caffeine breath test results and caffeine clearance were found [133][134][135][136].…”
Section: Exhaled Breathsupporting
confidence: 82%
“…We found only one previous report of the half-life of PBB in humans (13). This study gave a median estimate of 12 years with a range of 4.6-94.7 years.…”
mentioning
confidence: 58%
“…Additional scrum samples were drawn at other times from some members of the cohort for various reasons, including for use in follow-up studies performed from 1982 through 1987 and for additional tests at individuals' requests. Cohort members with higher initial PBB levels were more likely to have multiple measurements because they were oversampled in various follow-up studies (12). In 1997, a total of 2,262 women in the registry had at least one PBB measurement and 1,407 (62%) had two measurements.…”
Section: Study Populationmentioning
confidence: 99%